The Effect of Microstructure and Phase Composition of Ti-6Al-4V Titanium Alloy Hardened Surface Layer on Its Mechanical Properties; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Sinyakova E. Elena; Panin A. V. Alexey Viktorovich; Perevalova O. Olga; Kalashnikov M. P. Mark Petrovich (2018, 2018)
Title screen